PENGARUH KOMPETENSI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT PURNAMA INDONESIA SIDOARJO - LISA BINTARI, ANASTASIA; BUDIONO, (Jurnal Ilmu Manajemen (JIM), 2018)
An organization expects good employee performance to achieve company goals both short-term and long-term goals. Competence and career development are the variables used in improving employee performance. This study aims to analyze the influence of competence and career development on employee performance at PT Purnama Indonesia. The population in this study were all employees of PT Purnama Indonesia, amounting to 33 employees using saturated sample technique, so the entire population used as a sample of 33 employees who obtained by using questionnaire method. This type of research is quantitative research. The analysis technique used in this research is multiple linear regression analysis using SPSS version 22. The results of this study show that partially competence has a positive and significant effect on employee performance of PT Purnama Indonesia and career development have positive and significant effect to employee performance of PT Purnama Indonesia. Simultaneously competence and career development have a significant effect on employee performance of PT Purnama Indonesia. Keywords: employee performance, competence, career development